A hybrid binary artificial bee colony algorithm for the satellite photograph scheduling problem. Issue 8 (2nd August 2020) - Luo, Kaiping
ABSTRACT: The satellite photograph scheduling problem has attracted increasing attention owing to its difficulty of solution and remarkable economic importance. The optimization problem involves scheduling the on-board cameras of the Earth observation satellite to gain more profit from the oversubscribed photograph requests. To tackle the real-world problem, a hybrid heuristic algorithm is developed. The algorithm skilfully integrates the common genetic operators and a well-designed two-phase repair operator into the evolutionary framework of an artificial bee colony. The performance of the proposed algorithm is compared with that of three state-of-the-art metaheuristics on an open test suite consisting of 20 benchmark instances and a new test set composed of 10 randomly generated large-scale problems. The experimental results indicate that the proposed algorithm achieves the best performance.